‘But what for?’: On the potentials of acknowledging scholastic positionalities (Journal of the Digital Humanities Association of Southern Africa, 2023)
Topics around ‘big data’ have both the potential to connect and divide scholars. This paper seeks to highlight some of the conceptual and scholastic exclusions by outlining my experience of entering the DH discipline as an anthropologist. The question ‘but what for?’ that was posed to me at the first conference I attended with regards to my research approach inspired me to think through methodological positionalities more seriously, which tend to reproduce old dissociations of that which can be quantified from everyday experience. An outline of the historical developments of the discipline of anthropology serves as an illustration of how understandings of scholarship (and relationships to other fields of study) may shift over time - and yet become firmly linked to methodological approaches as well as scholarly identities. In making sense of what it means to live in an increasingly data-saturated world and to bring humanistic analysis in conversation with the digital, DH scholars have to take active steps in opening up conceptual frameworks and interdisciplinary communication. This also means including a wider range of humanities scholars and fringe DH views. Grappling with the shifting power dynamics and accelerated changes in lived experience prompted by digitisation, I suggest, should also involve critically engaging with how we as scholars think about ourselves in relation to the methods we use, and becoming comfortable with the idea of their/our incompleteness.
Keywords: Digital Humanities; Humanism; Incompleteness; Disciplinary hybridity; Knowledge production; Disciplinary Positionality; Methods